IMPLEMENTASI BUILDING INFORMATION MODELLING (BIM) PADA PERENCANAAN STRUKTUR GEDUNG PERKANTORAN DI KABUPATEN KARANGANYAR - Nurliinda, Yuliana; Purnamawanti, Dian Arumningsih Diah; Priyanto, Kusdiman Joko (Jurnal Teknik Sipil dan Arsitektur, 2026)
Modeling and analysis of building structures using the BIM (Building Information Modeling) Method is a concept in planning and implementation that is still rarely applied, this raises several questions such as how to apply the BIM Concept or what are the advantages and disadvantages of the BIM Method, things like this are the background why it is necessary to further review how to apply the BIM Method in a building construction planning. The application of the BIM Method needs to refer to the standard rules that apply in Indonesia, namely as well as supporting literature in terms of concepts and theories, standard rules in multi- storey building planning in Indonesia are regulated by SNI 1726, SNI 1727, and SNI 2847 where each part of this rule must be fulfilled in the planning part of a multi-storey building. The BIM method itself needs to be supported by software tools that are integrated with each other, for example Autodesk Revit for 3-dimensional modeling and Robot Structural Analysis Professional for conducting structural analysis in multi-storey building planning, the application of the BIM method at the planning stage produces 2dimensional, 3-dimensional modeling, element detailing and structural analysis.